Glutamate Signaling Pathway in Absence Epilepsy: Possible Role of Ionotropic AMPA Glutamate Receptor Type 1 Subunit - Zavvari, Fahime (Iran J Pharm Res, 2020)
AMPA receptors, consisting of glutamate receptor type1 (GluR1) subunit are involved in the pathophysiology of some neurological disorders. In this study, the role of the GluR1 subunit in the development, as well as features of absence seizures were assessed. Both Wistar and WAG/Rij (a genetic animal model of absence epilepsy) rats with 2 and 6-month ages were included in the study. The expression of GluR1 was measured in the somatosensory cortex. Moreover, the effects of pharmacological activation and inhibition of AMPA receptors on the characteristic of absence epileptic activities were evaluated by microinjection of agonist or antagonist of AMPA receptors on the somatosensory cortex in the epileptic WAG/Rij rats. Distribution of the GluR1 subunit of AMPA receptors in the both IV (p < 0.001) and VI (p < 0.01) layers of the somatosensory cortex in the epileptic WAG/Rij rats was higher than non-epileptic animals. In addition, the microinjection of AMPA receptors agonist on the somatosensory cortex of the WAG/Rij rats increased both amplitude (p < 0.01) and duration (p < 0.001) of spike-wave discharges (SWDs), while injection of antagonist reduced amplitude (p < 0.001) and duration (p < 0.01) of SWDs in the somatosensory cortex of epileptic rats. The high expression of GluR1 in the somatosensory cortex of epileptic rats suggests the role of AMPA receptors consisting of the GluR1 subunit in the development of absence seizures. The modulatory effects AMPA receptors on the feature of SWDs suggest the potential of AMPA receptors antagonists as a therapeutic target for absence epilepsy.